Mobile-Based Application Interventions to Enhance Cancer Control and Care in Low- and Middle-Income Countries: A Systematic Review - Andrew Donkor; Andrew Donkor; Andrew Donkor; Jennifer Akyen Ayitey; Prince Nyansah Adotey; Esther Oparebea Ofori; Doris Kitson-Mills; Verna Vanderpuye; Samuel Yaw Opoku; Tim Luckett; Meera R. Agar; Penelope Engel-Hills (Frontiers Media S.A., 2023)
Objective: To identify and appraise mobile-based application (mAPP) interventions that have been used to support cancer control and care in low- and middle-income countries (LMICs).Methods: Four electronic databases were systematically searched for studies that reported primary research findings related to mAPP interventions applied in oncology settings in LMICs. A narrative synthesis was performed using the Mhealth Index and Navigation Database as an analytical framework.Results: Twenty studies reporting 18 cancer control and care mAPPs were included in this review. Among these mAPPs, ten focused on prevention, screening and early detection of cancer, five provided information to optimise supportive and palliative care, two provided support to assist treatment-shared decision-making and one covered information for follow-up and survivorship care.Conclusion: Cancer mAPP interventions are gradually gaining attention in LMICs as they provide unique resources for empowering and strengthening the role of people with cancer in their own care. To enhance cancer control, a focus on prevention and early detection is important; however, more mAPP interventions related to cancer treatment, follow-up and survivorship are also needed to enable more cost-effective cancer care.